Disinfestation of stored wheat grain infested with Rhyzopertha dominica by ozone treatment: process optimization and impact on grain properties. (20th May 2019) - Mishra, Gayatri; Palle, Aphiya Amulya; Srivastava, Shubhangi; Mishra, Hari N
Abstract: BACKGROUND: Ozone is a highly oxidative gas that has a long history of safe use as a disinfectant and sanitizer from producers of pharmaceuticals and many other organic compounds. In the current work, disinfestation of stored wheat grain infested with a common insect, Rhyzopertha dominica, was attempted through ozone (O3 ) treatment as an alternative to chemical fumigants. RESULTS: The optimized treatment conditions for ozone fumigation of stored wheat grain were 12% (w/w) grain moisture, 2.5 g m −3 ozone concentration and 8 h of treatment. The mortality of R. dominica adults, pupae, larvae and eggs was 97, 100, 99 and 100%, respectively. Moisture and protein content of the ozone‐treated wheat was found to be lower as compared to infested wheat. Microstructural changes in the treated samples were clearly visible on scanning electron microscopy images, whereas minimal changes at the molecular level and of rheological parameters were evident based on Fourier transform infrared spectroscopy peak and rheometry data. CONCLUSION: Ozone was found to be an effective reagent for disinfestation, aimed at all life stages of R. dominica in stored wheat grain, that leaves no residue behind. Rotational strategies can be applied to obtain increased mortality while maintaining the usability of the grain for different purposes. © 2019 Society of Chemical Industry